The Status of the IS Field: Historical Perspective and Practical Orientation - Frederic Adam; Brian Fitzgerald (Information Research: An International Electronic Journal)
This paper provides a detailed assessment of the current status of the Information Systems (IS) field by tracing its historical evolution. It uses lessons drawn from the history of another social science, sociology, to highlight some of the fundamental choices now facing IS researchers. Firstly, the paper identifies the most important tensions and forces that shaped the evolution of the IS field in the 40 or so years of its history. Secondly, it draw a comparison between IS and sociology and uses some selected fundamental patterns of the history of the latter to explain the main aspects of the evolution of IS. Finally, noting that IS researchers do not seem to have succeeded in developing a core of concepts and definitions to enable the accumulation of knowledge in IS and to significantly contribute to the improvement of the business application of information systems, the paper calls for a debate on the future orientations of the field and identifies some of the choices that can be made at this stage of the evolution of the field.